Efeito de Trichoderma spp. no potencial fisiológico de sementes e mudas de melão - Cruz, Josiane Leila Gomes da (2010)
The objective of the present study was to evaluate the effect of Trichoderma spp. on the physiologic potential of seeds and melon seedlings and also to evaluate the effect of Trichoderma spp. in melon seeds through the inoculation technique of water restriction. Two experiments were accomplished: in the first one, they were used as treatment of seeds, biological products to the base of Trichoderma spp. in the formulation it liquid and powder, besides the fungicide Captan isolated SC® and associate to the biological products. In the second experiment the technique of water restriction was used, where the treatments consisted of: BDA; BDA + manitol - 0,6MPa; BDA + manitol -0,8MPa; Trichoderma spp.; BDA + manitol -0,6 MPa +Trichoderma spp; BDA + manitol -0,8MPa + Trichoderma spp. The physiologic quality of the seeds was evaluated by a group of tests accomplished in controlled conditions of laboratory and greenhouse. Trichoderma spp. it was shown to be efficient in the germination test and cold without soil. In the evaluation of melon seedlings, Trichodel® and Agrotrich® using half of the recommended dose, separately or associate to the chemical fungicide, they presented the best results. The manitol use -0,8MPa + Trichoderma spp. was shown higher to the other treatments in the germination tests and test of cold without soil. Therefore, the same result was not obtained when it was evaluated the seedlings. Therefore, the technique of the water restriction it wasn t efficient in the inoculation of Trichoderma spp.